Thyroid hormone regulates both melanin and non-melanin pigmentation in Sinibrama taeniatus via three types of chromophores - Liu, Xiaoqin; Wang, Siya; Feng, Qilin; Cheng, Linfeng; Teng, Ran; Wei, Lan; Wu, Yuanbing; Wang, Zhijian; Yuan, Dengyue (Frontiers in Marine Science, 2024)
Body color is a prominent phenotypic trait and a significant economic characteristic in fish. While current research mainly examines the effects of genetic factors, less emphasis has been placed on the role of endogenous hormones in fish body color. This study investigated the changes in phenotype, pigment content, and related gene expression in juvenile Sinibrama taeniatus after a 30-day treatment with gradient concentrations of L-thyroxine . The results showed that, compared to the control group, the body color of the low-concentration L-thyroxine treatment group (20 nM) was lighter, while that of the high-concentration group (40 nM and 80 nM) was darker. Thyroid hormone treatment simultaneously affected melanophores, xanthophores, and iridophores in different ways, leading to an increase of melanin and guanine, and a reduction of pteridine and β-carotene. These findings suggest that thyroid hormone regulates fish body color pigment synthesis through both melanin-based and non-melanin-based mechanisms. To further understanding of the regulatory roles of thyroid hormone on pigment synthesis, we investigated the expression changes in genes involved in melanin-based and non-melanin-based pigmentation under the different hormonal regimes. Expression of genes involved in melanin-based (e.g. ctnnb1, wnt10b, and adcy3) and non-melanin-based pigmentation (e.g. xdh, ltk, pnp4a, and mpv17) were modified by thyroid hormone treatment. Our results enhanced the understanding of the role of thyroid hormone in fish pigmentation and provide useful information for cultivating fish with desirable body colors in aquaculture.